1986
DOI: 10.1037/0022-3514.51.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Life events and substance use among adolescents: Mediating effects of perceived loss of control and meaninglessness in life.

Abstract: Throughout history, alcohol and other drugs have been used to provide relief in times of stress and frustration. Research has confirmed this association between disruptive life change events and substance use. It was hypothesized that two psychological constructs facilitate and mediate this relation between stress and substance use. Uncontrollable stress (negative life change events) was assumed to create a sense of loss of control, which in turn engendered a decreased level of meaning in life. This meaningles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
212
2
6

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(229 citation statements)
references
References 53 publications
9
212
2
6
Order By: Relevance
“…If, as our data indicate, stress can produce sensitization to exogenous cannabinoids like Δ 9 -THC, it is reasonable to postulate that physiological and psychological effects of acute cannabis intoxication could be potentiated in individuals experiencing adverse environmental stress. One result might be an increased likelihood of reuse or establishment of a self-medicating routine involving cannabis and/or other drugs of abuse (Butters, 2002;Newcomb and Harlow, 1986). Thus, it is noteworthy that CB 1 antagonists have found therapeutic applications in reducing recidivism in smokers (Cohen et al, 2005;Tucci et al, 2006) and other substance abusers (Maldonado et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…If, as our data indicate, stress can produce sensitization to exogenous cannabinoids like Δ 9 -THC, it is reasonable to postulate that physiological and psychological effects of acute cannabis intoxication could be potentiated in individuals experiencing adverse environmental stress. One result might be an increased likelihood of reuse or establishment of a self-medicating routine involving cannabis and/or other drugs of abuse (Butters, 2002;Newcomb and Harlow, 1986). Thus, it is noteworthy that CB 1 antagonists have found therapeutic applications in reducing recidivism in smokers (Cohen et al, 2005;Tucci et al, 2006) and other substance abusers (Maldonado et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…According to Wood and Bandura (1989, p. 408), "self-efficacy refers to beliefs in one's capabilities to mobilize the motivation, cognitive resources, and courses of action needed to meet given situational demands." Perceptions of efficacy have been shown to translate into positive behaviors in numerous domains such as dealing with phobias and anxieties (Bandura, Reese, and Adams1982), overcoming alcohol and drug abuse (Newcomb and Harlow 1986), and quitting smoking (DiClemente 1981). Furthermore, previous research has shown that people with a strong sense of self-efficacy are more persistent than their lowself-efficacy counterparts in the face of barriers to action (Bandura and Cervone 1983;Bernier and Avard 1986).…”
Section: Mechanism Underlying the Effectsmentioning
confidence: 99%
“…Likewise, Pires and Jenkins (2007) found that parental rejection was positively related to adolescent illicit drug use. In response to a perceived loss of self-esteem and control, as well as a sense of hopelessness, adolescents were found more likely to use drugs as an avenue to ''escape'' from the realities of their daily lives (Newcomb and Harlow 1986).…”
Section: Introductionmentioning
confidence: 99%